2009
DOI: 10.1111/igj.0b013e31819a1ce8
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Trial Participation Is Associated With Improved Outcome in Women With Ovarian Cancer

Abstract: Women with ovarian cancer who participate in clinical trials at this institution have improved survival compared with those who are treated with standard therapies. No other factors examined were associated with treatment completion or survival. Further, participation in clinical research does not vary by age, ethnicity, urban versus rural lifestyle, or cancer stage or histologic subtype. However, disclosure of this information to potential clinical trial participants may represent an ethical conflict and shou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
10
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(14 citation statements)
references
References 23 publications
4
10
0
Order By: Relevance
“…Due to the distinct nature of women's health we focused solely on this disease area and within this subgroup analyses we observed an effect not previously seen in overall syntheses. A retrospective study of a regional cancer centre in the USA found clinical trial participation to improve significantly the survival of women with ovarian cancer compared with non‐participants (median 46 versus 25 months, 95% CI 1.03–2.15 months, P = 0.03) . That paper, though not part of our meta‐analysis, reached the same conclusion as ours.…”
Section: Discussionsupporting
confidence: 79%
See 1 more Smart Citation
“…Due to the distinct nature of women's health we focused solely on this disease area and within this subgroup analyses we observed an effect not previously seen in overall syntheses. A retrospective study of a regional cancer centre in the USA found clinical trial participation to improve significantly the survival of women with ovarian cancer compared with non‐participants (median 46 versus 25 months, 95% CI 1.03–2.15 months, P = 0.03) . That paper, though not part of our meta‐analysis, reached the same conclusion as ours.…”
Section: Discussionsupporting
confidence: 79%
“…A retrospective study of a regional cancer centre in the USA found clinical trial participation to improve significantly the survival of women with ovarian cancer compared with non-participants (median 46 versus 25 months, 95% CI 1.03-2.15 months, P = 0.03). 62 That paper, though not part of our meta-analysis, reached the same conclusion as ours.…”
Section: Strengths and Limitationssupporting
confidence: 79%
“…Affluent individuals possess greater economic resources and social capital, which enable them to avail themselves of the treatment advances associated with better cancer survival [39,40]. In addition, individual-level affluence is associated with private health insurance [73], which is associated in turn with greater access to gynecologic oncologists [74] and participation in clinical trials [75], factors that also result in improved ovarian cancer survival [76,77]. …”
Section: Discussionmentioning
confidence: 99%
“…They may be especially important in the context of ovarian cancer (OC), a disease characterized by late-stage diagnosis [2], persistently high mortality rates [3,4], and high rates of drug resistance and tumor recurrence [2]. Clinical trials may expand the number of available treatment options for OC patients [5,6] while advancing scientific discovery.…”
Section: Introductionmentioning
confidence: 99%